Tác động của văn hóa tổ chức, sự nhận dạng tổ chức đến ý định ở lại và vai trò trung gian của cam kết tình cảm - Tran Thi Ai , Cam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study examines the effects of organizational culture and organizational identification on employees’ intention to stay along with the mediating role of affective commitment. By using quantitative approach for a sample of 734 employees working in 30 information technology (IT) enterprises in Vietnam selected from a survey which was conducted between April 2014 and July 2014, the results indicate that clan culture, adhocracy culture, hierarchy culture, group identification, and organizational identification are major and direct antecedents of affective commitment and their intention to stay. Furthermore, the relations that organizational culture and organizational identification have with employees’ intention to stay are mediated by affective commitment. Theoretical and managerial implications are accordingly drawn as principal recommendations for further research.
Keywords: Organizational culture; Intention to stay; Affective Commitment; Vietnam